Are we graduating physiotherapists with the burnout syndrome: Evaluating physiotherapy education at the University of the Western Cape - Seyi L. Amosun; Nokuzola D. Dantile (South African Journal of Physiotherapy, 1996)
Burnout has been identified in physiotherapists. Based on the postulation that burnout actually begins during physiotherapy educational training, this study set out to determine if burnout exists among physiotherapy students at the University of the Western Cape. Using a modified version of the Maslach Burnout Inventory, 80.3% of the study sample(N=76) were found to have moderate to high levels of emotional exhaustion, while 14,5% indicated moderate to high levels of depersonalisation. However, 72.4% reported moderate to high levels of personal accomplishment. Some factors which contributed to burnout were also reported. It was concluded that burnout existed in the subjects involved in the study.